Assessing English reading comprehension by Chinese EFL learners in computerized dynamic assessment - Yanfeng Yang; David D. Qian (Language Testing in Asia, 2017)
Abstract Background Predicated on Vygotsky’s zone of proximal development (ZPD), dynamic assessment (DA) integrates teaching with assessment in a single activity by providing mediation to help learners perform beyond their independent functioning and simultaneously promote learner development. It advantages over traditional psychometric tests in that DA can not only reveal the learners’ actual level of development from their independent performance as what the traditional tests did but also their potential level of development from the mediations the learners need during the mediator-learner interactions. However, the number of learners a DA assessor can help is limited due to the time demand of mediator-learner interactions. To overcome this weakness, researchers are turning to computerized dynamic assessment (C-DA). Methods The study aimed to find out the learners’ difficulties in reading comprehension, the effects of C-DA and the learners’ reflections on the C-DA program. Multiple choice questions in the reading comprehension section were adapted from CET4 (College English Test, Band 4). Two groups of students participated in the present study. In the pilot study, a group of students were asked to write down their thinking process after they finished a reading test, from which the students’ difficulties in reading comprehension test were identified and mediations were worked out afterwards. The mediation levels and the scoring scale were also determined and put into the C-DA program devised for the main study. Another group of students were asked to do a reading test using C-DA. After the test, a learner profile capturing the students’ performances in the test was generated from the program. Finally, a questionnaire was distributed to collect data for the students’ reflections on C-DA. Results It was found that the learners mainly encountered three difficulties in their reading comprehension test: (1) new words were the biggest barrier; (2) learners felt hard to locate on the relevant sentences in the original passage from the information provided in the question; (3) their inferential abilities are weak. The analysis of the data generated by the C-DA program indicated that C-DA far exceeded the traditional static assessment for its stronger diagnostic capacities and the deeper insights it provided for subsequent teaching. The results of the questionnaire showed that C-DA was greatly welcomed by the students and believed to be particularly helpful in building up confidence for those low achievers as identified in traditional static assessment. Conclusions The major contribution of the present study was to implement DA principles to larger scale study with the use of computer technology and gain valuable insights for future studies. However, limitations remained and future studies should try to address the issues discussed in the present study.